Credit Constraints and Job Mobility - Hagstrom, Paul A.; Owen, Ann L. (Journal of Income Distribution®, 2008)
We estimate the probability of voluntary job change using data from the Panel Study of Income Dynamics (PSID) and imputed values for several different measures of financial stress from the Survey of Consumer Finances (SCF). Our main finding is that single men are more likely to respond to credit constraints by voluntarily switching jobs. For married men, the effect depends on the type of financial stress experienced. Our results suggest that the higher rate of job mobility among single men can be attributed to both higher incidence of credit constraints among this group as well as a differential response to these constraints.